Parasitism in Children Aged Three Years and Under: Relationship between Infection and Growth in Rural Coastal Kenya. - A Desiree LaBeaud; Monica Nayakwadi Singer; Maxim McKibben; Peter Mungai; Eric M Muchiri; Elisabeth McKibben; Ginny Gildengorin; Laura J Sutherland; Charles H King; Christopher L King; Indu Malhotra (Public Library of Science (PLoS), 2015)
BACKGROUND:Parasitic infections, which are among the most common infections worldwide, disproportionately affect children; however, little is known about the impact of parasitic disease on growth in very early childhood. Our objective was to document the prevalence of parasitic infections and examine their association with growth during the first three years of life among children in coastal Kenya. METHODOLOGY/PRINCIPAL FINDINGS:Children enrolled in a maternal-child cohort were tested for soil transmitted helminths (STHs: Ascaris, Trichuris, hookworm, Strongyloides), protozoa (malaria, Entamoeba histolytica and Giardia lamblia), filaria, and Schistosoma infection every six months from birth until age three years. Anthropometrics were measured at each visit. We used generalized estimating equation (GEE) models to examine the relationship between parasitic infections experienced in the first three years of life and growth outcomes (weight, length and head circumference). Of 545 children, STHs were the most common infection with 106 infections (19%) by age three years. Malaria followed in period prevalence with 68 infections (12%) by three years of age. Filaria and Schistosoma infection occurred in 26 (4.8%) and 16 (2.9%) children, respectively. Seven percent were infected with multiple parasites by three years of age. Each infection type (when all STHs were combined) was documented by six months of age. Decreases in growth of weight, length and head circumference during the first 36 months of life were associated with hookworm, Ascaris, E. histolytica, malaria and Schistosoma infection. In a subset analysis of 180 children who followed up at every visit through 24 months, infection with any parasite was associated with decelerations in weight, length and head circumference growth velocity. Multiple infections were associated with greater impairment of linear growth. CONCLUSIONS/SIGNIFICANCE:Our results demonstrate an under-recognized burden of parasitism in the first three years of childhood in rural Kenya. Parasitic infection and polyparasitism were common, and were associated with a range of significant growth impairment in terms of weight, length and/or head circumference.